Sekolah Keorangtuaan Bagi Ayah Anak Usia Dini Berstatus Single Parent Sesuai Pedoman Hidup Islami Warga Muhammadiyah - M. Fadlillah; Ida Yeni Rahmawati (Universitas Mathla'ul Anwar Banten, 2022)
PARENTING SCHOOL FOR FATHERS OF EARLY CHILDHOOD WITH SINGLE PARENT STATUS ACCORDING TO THE LIFE GUIDELINES FOR MUHAMMADIYAH CITIZENS. Early childhood care in Ponorogo Regency still has many problems. The high number of migrant workers who are dominated by mothers makes child care less than optimal because it is completely left to fathers. Early childhood are raised by single father so that children's rights are not well served. This parental school aims to provide understanding to parents, especially fathers, in nurturing and caring for their children. The method of this service activity is in the form of training and seminars on appropriate parenting for early childhood development. This service activity involves doctors, academics, and Muhammadiyah activists as resource persons. The results of the service showed that there were 15 fathers of early childhood who attended the parental school which was held on November 14, 2021. They were very enthusiastic in participating in this activity from beginning to end. The materials given to the participants were early childhood growth and development, parenting typology, and child education in Islam. It is hoped that through this program fathers can care for, nurture, and raise their children well in accordance with Islamic religious guidance.